2016
DOI: 10.1039/c6cc04052g
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-induced highly efficient synthesis of boron doped reduced graphene oxide for supercapacitors

Abstract: In this work, we presented a novel route to synthesize boron doped reduced graphene oxide (rGO) by using the dielectric barrier discharge (DBD) plasma technology under ambient conditions. The doping of boron (1.4 at%) led to a significant improvement in the capacitance of rGO and supercapacitors based on the as-synthesized B-rGO exhibited an outstanding specific capacitance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(47 citation statements)
references
References 43 publications
0
46
0
Order By: Relevance
“…Work on dry plasma reduction of surfaces by plasma jet [32] and radio frequency (RF) discharges [48] has also been reported. [50] Further,s imilars ignificant progress in dry plasma reduction by DBD was reported by Chuang et al, [51] who used atmospherich ydrogen/nitrogen plasma to treat TiO 2 powders.H owever the DBD systems presented in Refs. Therefore, if plasma is to be used in such processes, its source should generate large-area plasma [49] with ah ighd egree of homogeneity and diffusivity.L ie tal.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Work on dry plasma reduction of surfaces by plasma jet [32] and radio frequency (RF) discharges [48] has also been reported. [50] Further,s imilars ignificant progress in dry plasma reduction by DBD was reported by Chuang et al, [51] who used atmospherich ydrogen/nitrogen plasma to treat TiO 2 powders.H owever the DBD systems presented in Refs. Therefore, if plasma is to be used in such processes, its source should generate large-area plasma [49] with ah ighd egree of homogeneity and diffusivity.L ie tal.…”
Section: Introductionmentioning
confidence: 64%
“…However,m ost of the atmospheric plasma sourceso perate with as mall area of generated plasma and are suited to only laboratory purposes.T he emerging fieldo ff lexible electronics requires high throughputm anufacturing with high efficiencies and low processing times. [50] and [ 51] involved certaind rawbacks if continuous treatment of large areas, particularly on flexible surfaces, were to be envisaged. employed atmosphericd ielectric barrierd ischarge (DBD)i nacoaxial electrode configuration to produce boron-doped rGO by using an H 2 plasma process.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, Shaobo et al reported boron doped reduced GO (B‐rGO) synthesized from a facile dielectric barrier discharge (DBD) plasma approach using boric acid as a boron precursor under ambient conditions. The boron content in B‐rGO was found to be 1.4%.…”
Section: Heteroatom‐doped Graphenementioning
confidence: 99%
“…In a case where B-doped graphene is synthesized at a lower growth temperature (900°C-1200°C), different boron configurations such as boronic acids, boronic, and borinic esters ( Figure 5) are produced. 258 In 2016, Shaobo et al 259 reported boron doped reduced GO (B-rGO) synthesized from a facile dielectric barrier discharge (DBD) plasma approach using boric acid as a boron precursor under ambient conditions. The boron content in B-rGO was found to be 1.4%.…”
Section: Boron-doped Graphenementioning
confidence: 99%
“…[19] To furnish a reasonable solution for this issue, doping of heteroatom over graphene framework is an effective approach. [24] Based on theoretical studies, B-doped graphene is reported as promising electrode for potassium ion battery. [20] Niu et al synthesized the boron doped graphene having boron content of 4.7 at % via pyrolysis between graphene oxide and boric acid at 900°C and achieved the specific capacitance of 173 F/g at 0.5 A/g current density.…”
Section: Introductionmentioning
confidence: 99%